Casca do grão de soja e/ou grão de aveia branca na terminação de novilhos confinados - Joner, Guilherme (2014)
The creation of beef cattle in Brazil is growing every year we move forward due to improved production rates. One of the maids to the increase of these indices is the feedlot technologies. For animal feed are used with alternative energy foods market availability, as the shell of soybean and oat grain. This study was conducted to evaluate the shell of soybean and oat grain as a sole source or associated in concentrate on performance and feeding behavior of feedlot finished steers fraction. 36 steers with initial age of 20 months and average weight of 226 kg. The treatments were: soybean hull (concentrated fraction formed basically by shell soybean), oat grain (concentrate fraction formed primarily by grain oat) and mixture (concentrated fraction formed by pieces of husk from the grain equal soy beans and oat). The diet was composed of 50 % sorghum silage and 50 % concentrate on dry matter. The experimental design was completely randomized with the animal performance data were subjected to analysis of variance and F test using PROC GLM and means were compared by Student's ``t´´ test, α = 0.05 probability. Have animal data feeding behavior were compared using the PROC MIXED procedure with repeated measures on time and the means were compared by least significant difference test. Animals fed soybean hull consumed 1.597 % of body weight in neutral detergent fiber. Have animal treatment oat grain consumed in ether extract 0.085 % of live weight. The daily live weight gain of the animals did not differ (mean 0.984 kg/day), and the bark treatment of soybean obtained this result by best rumination efficiency of neutral detergent fiber (655.61 g/h), different treatment of oat grain that obtained by the total lipids. The dry matter intake was not altered by neutral detergent fiber content in this work. Both the bark of soybean as the oat grain provides similar performance in finishing beef cattle feedlot. Animals of the mixture showed higher feeding time (264 minutes), increased number of daily meals, less time ruminating (447.12 minutes), less time spent chewing (477.67 minutes), number of chewed by day and cake (59.59 and 28.667). Resulting in improved efficiency of rumination as dry matter, neutral detergent fiber.